Implementasi Enterprise Resource Planning ODOO Untuk UMKM Studi Kasus Raturatus - Sulistiami, Julmi; Nopiana, Medi (Jurnal Ilmiah Wahana Pendidikan, 2024)
The rapid development of existing technology challenges the business world to be able to develop its business. Information technology is a way for companies to compete in the era of technological development like today. RatuRatus is a producer of processed spices and herbs that implements information technology into its business. The level of company data problems that are quite complex makes RatuRatus use Odoo to overcome these problems. Odoo is an Enterprise Resource Planning-based software that is open source so that it is used by companies that are just digitizing themselves. Through Odoo RatuRatus can develop several modules, namely the Inventory Module, Purchase Module, Manufacturing Module, Sales Module, and Accounting Module so that company data can be integrated efficiently, effectively, and the company will not experience data loss.